EFEK PENAMBAHAN MINYAK KEDELAI TERHADAP KARAKTERISTIK ORGANOLEPTIK DAN KANDUNGAN OMEGA-6SUSU PASTEURISASI - Angela Nitia Nefasa; Anang Mohamad Legowo; Ahmad Nimatullah Al-Baarri (Jurnal Pangan dan Gizi, 2013)
The purpose of the study to determine the effect of the addition of soybean oil with different levels of the organoleptic characteristics and the effect of increased omega-6 content of pasteurized milk. Research material that is derived from cow's milk a cow shed in the Faculty of Animal Husbandry and Agriculture,  Diponegoro University and soybean oil from one of the markets in the city of Semarang. The addition of soybean oil into a fresh cow's milk, then pasteurized using LTLT (63oC, 30 min). The results showed the addition of soybean oil can increase the content of omega-6 in pasteurized milk. Signifcantly of the addition of soybean oil to the organoleptic odor, whereas taste and color are not significant. Increased levels of omega-6 highest in pasteurized milk obtained from the addition of soybean oil as much as 0.45% with ratio 3.2: 1. Increased levels of omega-6 still has not reached 4: 1. The addition of antioxidants in milk pasteurization aims to prevent oxidation. Feed silage tend to increase the risk of oxidation, the milk used should not be obtained from cows fed silage.